Application Design Library With gamification concept - Barokati, Nisaul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Abstract: The library is an effort to maintain and improve the efficiency and effectiveness of the learning process. Various means have been used to enhance the librarys role in community development. One way is to develop a concept and a different orientation in the management system or the library. The concept in question is gamification. Gamification is a process with the aim of changing jobs or activities that usually go tedious and less enjoyable to be more interesting and fun to do. One approach taken is to reward both virtual and non-virtual that can increase peoples motivation to do something, in this case, is to visit and take advantage of the functions and library facilities. This research resulted in a model that features a library application with the concept of gamification. The model can be implemented into an application that will increase visits and activities at the library. Thus the function and the main purpose of the library be met..